Petrografia, litoquímica e idades Ar-Ar de diques máficos mesozóicos (e cambrianos?) de Minas Gerais: comparações com basaltos da Província Paraná-Etendeka e com diques da Suíte Fundão - Raphael Martins Coelho (2016)
This work deals whit the mesozoic mafic dyke swarms and possible representative of undeformed cambrian mafic dykes in Brasiliano mobile belts of the Minas Gerais State. It Will be presented in the form of two papers. The first paper deals with the Ar-Ar geochronology of cretaceous dykes crossing the São Francisco Craton and its surrounding Brasiliano móbile belts, which are the Transminas and Serra do Mar mafic dyke swarms. Plateau age of 124.56 ± 2.15 Ma and inverse isochron age of 131.92 ± 3.63 Ma for a Serra do Mar dyke and plateau age of 135.72 ± 4.35 Ma and inverse isochron age of 128.43 ± 8.46 Ma for a Transminas dyke, insert in the same context of the intense magmatic event related to the fragmentation of the western part of the Gondwana supercontinent, initiating the development of the Brazilian and African continental margins and the opening of the South Atlantic Ocean. This magmatism is represented by basaltic flows and mafic dyke swarms of the huge province igneous Paraná (Brazil) - Etendeka (Africa) 133-135 Ma. The second paper deals with the petrographic and lithochemical characterization of the Transminas and Serra do Mar dykes in Minas Gerais (MG), as well as with possible representatives of Cambrian dykes, the so-called Fundão Suite, described in Espírito Santo (ES). Macroscopically, all these rocks are fine-grained grey dolerites similar to each other and keep subophitic texture. However, cretaceous dykes are Olivine gabbros/Olivine basalts with essential mineralogy composed of plagioclase, clinopyroxene and olivine and Cambrian dykes keeps plagioclase, clino- and orthopyroxene without olivine, therefore gabbro norites. Lithochemically, all these dykes are tholeiitic basalts with some degree of crustal contamination, and the Cretaceous are high Ti and the Cambrian are low Ti. Only two dykes belonging to the Serra do Mar swarm are alkaline trachy-basalts. The spidergrams of incompatible and rare earth elements of the Cretaceous dykes show similarities with basalts of the Paraná-Etendeka province, following the OIB pattern, typical ofmantle plumes. The Cretaceous dykes of MG correlate geochronological, petrographic and lithochemically to the basalts of Paraná-Etendeka province. This Cretaceous magmatism derived from a garnet lherzolite source, related to the geodynamic context possibly linked to the activity of Tristan da Cunha mantle plume. The Cambrian dykes, both in MG and in ES, are petrographic and lithochemically similar each other and keep signature of enriched ocean ridge basalts. Dykes of the Fundão Suite derived from a spinel lherzolite source and are related to the gravitational collapse of Araçuaí Orogen.